PROTEOMIC COMPARISON OF EXTRACELLULAR MATRIX WITHIN LIVER METASTASES OF COLORECTAL CANCER AND NORMAL LIVER - ARSENIY E. Yuzhalin; RUTH J. Muschel (Фундаментальная и клиническая медицина)
Aim. To investigate the composition of extracellular matrix proteins in colorectal cancer liver metastases and normal liver. Materials and Methods. Following decellularization of the extracellular matrix using a specific cocktail of detergents, we examined protein content of metastatic and normal liver tissues by means of mass-spectrometry and immunofluorescence staining. Results. Proteomic analysis revealed significant differences in the expression of extracellular matrix proteins between cancerous tissue and normal liver. Results of masspectrometry were verified by immunofluorescence staining to the relevant proteins. Conclusion. Qualitative and quantitative composition of extracellular matrix proteins substantially differs between colorectal cancer liver metastases and normal liver.